2016
DOI: 10.1007/s00267-016-0800-5
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Forest and Phylogenetic Structure in Abandoned Cocoa Agroforestry in the Atlantic Forest of Brazil

Abstract: Cocoa agroforests like the cabrucas of Brazil's Atlantic forest are among the agro-ecosystems with greatest potential for biodiversity conservation. Despite a global trend for their intensification, cocoa agroforests are also being abandoned for socioeconomic reasons especially on marginal sites, because they are incorporated in public or private protected areas, or are part of mandatory set-asides under Brazilian environmental legislation. However, little is known about phylogenetic structure, the processes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 60 publications
0
8
0
3
Order By: Relevance
“…Many studies compared the potential for conservation of different animal and plant species among different types of cacao agroforest, such as cabruca, rubber agroforest (cacao shaded by rubber trees-Hevea brasiliensis) and Erythrina agroforestry (cacao shaded by Erythrina glauca or Erythrina fusca). The majority of these studies concluded that cacao agroforests with a more complex and diverse vegetation structure, being mainly shaded by native trees, were better able to maintain subsamples of the communities found in the adjacent forests than the monodominant agroforests [101,110,121,122]. The presence of large-diameter native trees was also pointed out as an important attribute for habitat use of mammal species in cabrucas [113].…”
Section: Habitat and Gene Poolmentioning
confidence: 99%
“…Many studies compared the potential for conservation of different animal and plant species among different types of cacao agroforest, such as cabruca, rubber agroforest (cacao shaded by rubber trees-Hevea brasiliensis) and Erythrina agroforestry (cacao shaded by Erythrina glauca or Erythrina fusca). The majority of these studies concluded that cacao agroforests with a more complex and diverse vegetation structure, being mainly shaded by native trees, were better able to maintain subsamples of the communities found in the adjacent forests than the monodominant agroforests [101,110,121,122]. The presence of large-diameter native trees was also pointed out as an important attribute for habitat use of mammal species in cabrucas [113].…”
Section: Habitat and Gene Poolmentioning
confidence: 99%
“…High litter production in the abandoned AFS may be due to the riparian vegetation structure ( Gonçalves Júnior et al, 2014 ; Rezende et al, 2017a ) and successional stage during forest recovery ( Sambuichi & Haridasan, 2007 ; Rolim et al, 2017 ). Factors such as abundant deposits of crop biomass ( Beer et al, 1998 ), which are related to high carbon stocks in the soil ( Gama-Rodrigues et al, 2010 ; Costa et al, 2018 ), and rapid nutrient cycling in these systems ( Nair et al, 1999 ) are likely to play a role.…”
Section: Discussionmentioning
confidence: 99%
“…A conversão de florestas tropicais em outros tipos de habitat como pequenos fragmentos, pastagens ou áreas agrícolas, com o objetivo de acessar bens de consumo providos pela biodiversidade ou para utilização do espaço, têm alcançado elevadas taxas nos últimos anos e causado a extinção de inúmeras espécies (Harvey et al 2008, Cassano et al 2009, Piasentin & Gois 2016, Rolim et al 2016. Para diminuir a perda de biodiversidade e ainda suprir as necessidades humanas de produtos agrícolas, a importância de sistemas produtivos menos impactantes, que preservam parcialmente a biodiversidade destas florestas, vem sendo reconhecida internacionalmente por estudos recentes (Harvey et al 2008, Gardner et al 2009, Piasentin & Gois 2016, Rolim et al 2016.…”
Section: Introductionunclassified
“…Para diminuir a perda de biodiversidade e ainda suprir as necessidades humanas de produtos agrícolas, a importância de sistemas produtivos menos impactantes, que preservam parcialmente a biodiversidade destas florestas, vem sendo reconhecida internacionalmente por estudos recentes (Harvey et al 2008, Gardner et al 2009, Piasentin & Gois 2016, Rolim et al 2016. Tais estudos reconhecem que a conservação não pode depender exclusivamente da preservação de ecossistemas sem qualquer forma de exploração.…”
Section: Introductionunclassified
See 1 more Smart Citation